2014
DOI: 10.1371/journal.pone.0092781
|View full text |Cite
|
Sign up to set email alerts
|

Red Light Represses the Photophysiology of the Scleractinian Coral Stylophora pistillata

Abstract: Light spectrum plays a key role in the biology of symbiotic corals, with blue light resulting in higher coral growth, zooxanthellae density, chlorophyll a content and photosynthesis rates as compared to red light. However, it is still unclear whether these physiological processes are blue-enhanced or red-repressed. This study investigated the individual and combined effects of blue and red light on the health, zooxanthellae density, photophysiology and colouration of the scleractinian coral Stylophora pistilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 41 publications
7
38
1
Order By: Relevance
“…Controlled laboratory studies have shown that captive corals subjected to shorter wavelengths in the~blue region (~400 to~500 nm) have high growth and photosynthesis rates [28,29]. As previously mentioned, we found relatively high values of total absorption (ap + ag) in the water column at shorter wavelengths (~400 to~500 nm) for our study sites, resulting in lower light levels at these wavelengths reaching the coral community.…”
Section: Discussionsupporting
confidence: 69%
“…Controlled laboratory studies have shown that captive corals subjected to shorter wavelengths in the~blue region (~400 to~500 nm) have high growth and photosynthesis rates [28,29]. As previously mentioned, we found relatively high values of total absorption (ap + ag) in the water column at shorter wavelengths (~400 to~500 nm) for our study sites, resulting in lower light levels at these wavelengths reaching the coral community.…”
Section: Discussionsupporting
confidence: 69%
“…In agreement with a wavelength-dependent screening function of the CFPs, both morphs displayed comparably intense signs of light stress when they were illuminated with orange light outside of the spectral window covered by the protective host pigment. Orange-red light has been shown to negatively affect the photophysiology of Symbiodinium in coral tissues (Smith et al, 2013;Wijgerde et al, 2014). The comparable susceptibility of the two morphs to photodamage in this spectral range supports the conclusion that higher resilience of the HF morph under blue light stress is due to the screening by the CFP rather than by other photoprotective mechanisms that might be more dominant in this morph.…”
Section: Discussionmentioning
confidence: 68%
“…The capacity of the CFPs to exert a photoprotective function by selective screening of symbionts in the blue spectral range was assessed by exposing the corals to either blue or orange-red light. Orange-red light was chosen for the control treatment as it is not absorbed by the CFPs and should therefore negatively affect both the high and low fluorescent morphs due to the detrimental effect of this waveband on algal photosynthesis (Smith et al, 2013;Wijgerde et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…fragments. The utilization of light with specific wavelengths spectra, is to date poorly studded, however the few studies existing are contradictory Wijgerde et al (2014), when using illuminations of white, blue and red spectrum found a negative response on the coral Stylophorapistillata, showed an negative response of coral fragments exposed to red light and a positive response in blue light. However, Kinzie and Hunter (1987) found no differences in Montiporaverrucosa response when fragments were exposed to different lighting, white and blue.…”
Section: Discussionmentioning
confidence: 99%